First Evidence of Correlation Between Evapotranspiration and Gravity at a Daily Time Scale From Two Vertically Spaced Superconducting Gravimeters. Issue 24 (22nd December 2021) - Carrière, Simon D.; Loiseau, Bertille; Champollion, Cédric; Ollivier, Chloé; Martin‐StPaul, Nicolas K.; Lesparre, Nolwenn; Olioso, Albert; Hinderer, Jacques; Jougnot, Damien
Abstract: Estimating evapotranspiration (ET) is a primary challenge in modern hydrology. Hydrogravimetry is an integrative approach providing highly precise continuous measurement of gravity acceleration. However, large‐scale effects (e.g., tides, polar motion, atmospheric loading) limit the fine time‐scale interpretation of the gravity data and processing leads to residual signal noise. To circumvent this limitation, we exploited the difference between two superconducting gravimeters (SGs) vertically spaced by 512 m. The gravity difference allows to remove common large‐scale effects. Daily variation of the gravity difference is significantly correlated with daily evapotranspiration as estimated using the water balance model SimpKcET (p‐value = 4.10 −10 ). However, this approach is effective only during rain‐free periods. In the future, comparison with direct ET measurements (e.g., eddy‐covariance, scintillometer) may confirm and strengthen our interpretation. Improved hydrogravimetric data processing could extend the proposed approach to other experimental sites equipped with a single SG. Plain Language Summary: Land evaporation and vegetation transpiration are crucial parameters in ecohydrology because evapotranspiration constitutes more than two‐thirds of precipitated water at the continental scale. However, this invisible flux is difficult to characterize, especially at kilometric scale, and its quantification is challenging for the hydrologist community. Continuous gravity monitoring using a superconducting gravimeter is a direct estimation of the mass change of lands with high precision. At a mountain site in southern France, we highlight a significant association between evapotranspiration calculated by a numerical model and the mass loss of the mountain. This approach provides a novel way to monitor evapotranspiration that will reinforce traditionally used methods. Key Points: For the first time, two vertically spaced gravimeters allow to interpret small gravity hydrologically induced signal (<5 nm/s²) Superconducting gravimetric signal are correlated with evapotranspiration at daily time step Gravimetry enables an integrative estimate of evapotranspiration particularly relevant for hydrology